1982
DOI: 10.1055/s-2007-971395
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating Properties of 5,20α(R)-Dihydroxy-6α,7α-epoxy-1-oxo-(5α)-witha-2,24-dienolide and Solasodine

Abstract: 5,20a (R)-Dihydroxy-oct,7a-epoxy-1-oxo-(5a)-witha-2,24-dienolide and solasodine inhibit proliferation of murine spleen cell cultures. The steroidal lactone occurs in the medicinal plants Withania somnifera and Lycium chinense. The steroidal alkaloid is contained inter alia in Solanum nigrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 4 publications
2
15
0
Order By: Relevance
“…Similar activity was also shown by withanolide D (68). The immunosuppressive effect of Lycium substance A (5) was demonstrated by BAHRand HANSEL (252) who studied its ability to inhibit proliferation of murine spleen cell cultures. The glycowithanolides, sitoindoside IX (61) and sitoindoside X (62), were shown to exhibit adaptogenic and immunostimulatory activity.…”
Section: Biological Activity Of Withasteroidssupporting
confidence: 52%
“…Similar activity was also shown by withanolide D (68). The immunosuppressive effect of Lycium substance A (5) was demonstrated by BAHRand HANSEL (252) who studied its ability to inhibit proliferation of murine spleen cell cultures. The glycowithanolides, sitoindoside IX (61) and sitoindoside X (62), were shown to exhibit adaptogenic and immunostimulatory activity.…”
Section: Biological Activity Of Withasteroidssupporting
confidence: 52%
“…Mors et al [7] has observed a striking parallelism between the capability of plants and their chemical components, which are antiinflammatory and antihepatotoxic as well as neutralizing the snake venom toxicity. The extracts of W. somnifera are reported to contain Withanolides, Withanolide glycosides, C-28 steroid lactones, saccharose, b-sitosterol, and macromolecules [39][40][41]. Most of the compounds noted above have structural similarities to compounds mentioned earlier and also possess antiinflammatory, antihepatotoxic, and immunomodulatory activities [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…(Solanaceae) have long been used as Rasaayana drugs in Ayurveda to prevent or treat disease through the restoration of a healthy balance of life forces and an integrated relationship to the environment (Sharma, 1983;Shukla and Thakur, 1991). Withaferin-A and withanolide-D from W. somnifera have been reported to possess immunosuppressive activity (Shobat et al, 1978;Bahr and Hansel, 1982). However, an adaptogen would be expected to induce immunosurveillance rather than the immunosuppression produced by the withanolide aglycones (Solomon et al, 1985).…”
Section: Introductionmentioning
confidence: 99%